Answer:
[tex]v(1) = 2\ ft/s[/tex]
Step-by-step explanation:
Given
[tex]s(t) = 4t^2-5t+3[/tex]
Required
Determine the instantaneous velocity at [tex]t = 1[/tex]
First, we need to determine s(1)
[tex]s(t) = 4t^2-5t+3[/tex]
[tex]s(1) = 4(1)^2 - 5(1) + 3[/tex]
Evaluate all brackets
[tex]s(1) = 4*1 - 5*1 + 3[/tex]
[tex]s(1) = 4 - 5 + 3[/tex]
[tex]s(1) = 2[/tex]
Next; v(t) is calculated as thus;
[tex]v(t) = \frac{s(t)}{t}[/tex]
Substitute 1 for t
[tex]v(1) = \frac{s(1)}{1}[/tex]
Substitute 2 for s(t)
[tex]v(1) = \frac{2}{1}[/tex]
[tex]v(1) = 2\ ft/s[/tex]